Women's Double Burden: Environmental Responsibility and Gender Inequality - Rosihan Khalik; Yossi Permata (Journal of Sumatera Sociological Indicators, 2024)
ABSTRACT Women's double burden is a complex global phenomenon, where women often bear double responsibilities in both the domestic and public spheres. This research analyzes how this double burden is exacerbated by environmental responsibility and reinforced by gender inequality. Through a literature review and case studies, this research reveals the complex dynamics between gender, environment, and work, and their implications for women's well-being. Keywords: Gender, inequality, patriarchy, ABSTRAK Beban ganda perempuan merupakan fenomena global yang kompleks, di mana perempuan seringkali menanggung tanggung jawab ganda baik di ranah domestik maupun publik. Penelitian ini menganalisis bagaimana beban ganda ini diperparah oleh tanggung jawab lingkungan dan diperkuat oleh ketimpangan gender. Melalui tinjauan literatur dan studi kasus, penelitian ini mengungkap dinamika kompleks antara gender, lingkungan, dan pekerjaan, serta implikasinya bagi kesejahteraan perempuan. Keyword: Gender, Ketimpangan, patriaki,